FINANCIAL DISTRESS AND INDONESIAN MANUFACTURING STOCK PRICES: A ZMIJEWSKI-GROVER MODEL - Hirman, Akhmad Akram; Taskurun; Al Qadri, Andi Ramdan (Berkala Akuntansi dan Keuangan Indonesia, 2025)
This study aims to test and analyze the effect of financial distress on stock prices using two models, namely Zmijewski (1984) and Grover (2001), on manufacturing companies, especially in the textile sector, electronic and computer products, automation and transportation, paper, and chemical products. This research design is Descriptive Statistics. The sample consisted of 53 manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2023, with 318 data. The sampling method used is a quantitative descriptive technique. The data analysis method applied is multiple linear regression analysis. The results showed that financial distress, as measured by two models, namely Zmijewski (1984) and Grover (2001), has a significant negative effect on stock prices, where the X-score value has a more significant influence than the G-score in reducing the stock price.